Human papillomavirus in cervical cancers of Malaysians - Cheah, P.L.; Looi, L.M.; Sivanesaratnam, V. (National Center for Biotechnology Information, 2011)
With a cervical carcinoma remaining the second leading cancer among Malaysian women, it is imperative to clarify the prevalence of human papillomavirus (HPV)in this respect, considering the death of local information.